NURSING CARE FOR CHILDREN WITH PEDIATRIC MULTISSYSTEMIC INFLAMMATORY SYNDROME - de Lucena Viana Alves, Letícia; Gilvandra de Souza Dantas, Walkiria; Carolina Salustino, Maria; Allyson Gomes Ferreira, Jefferson; Rodrigues Pereira, Patrícia; de Castro Cardoso, Jéssica; Gomes de Souza Silva, Lúcia (Health and Society, 2023)
Objective: to evidence from the scientific literature the clinical and therapeutic characterization of children with Pediatric Multisystem Inflammatory Syndrome and definition of their respective diagnostic diagnoses; Method: the study is configured as a scope review, it is organized by the Preferred Reporting Items for Systematic Review and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) in which it is proposed by the Joanna Briggs Institute; Results: 34 articles were identified after a sample in the databases, and after the selection of data inclusion and exclusion of 16 final articles; Final considerations: Nursing care for children and adolescents with SIM-P is still unexplored and has limited scientific evidence. In addition, nurses should be aware of updates on a thorough clinical assessment, including anamnesis, physical examination, epidemiological link with suspected or confirmed cases of COVID-19 in the 2nd to 4th week prior, in addition to Complementary tests to assess the process. inflammation and the recovery of organs, to early identification and treatment, having as vital functions.